2018
DOI: 10.29252/ijrm.16.8.501
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the expression levels of miR-135a and HOXA10 gene in the eutopic and ectopic endometrium

Abstract: Background:The study of microRNA expression can be effective in the diagnosing and treating different diseases. miR-135a is one of the most important micro-ribonucleic acids involved in endometriosis. Among the genes that become the target of the miR-135a and are subjected to changes in the endometrium of patients with endometriosis is HOXA10 gene which is expressed in the endometrium in response to steroid hormones.Objective: The aim of this study was to evaluate the expression of miR-135a and its relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…In the biggest study, which included 50 controls and 32 eutopic samples, elevated levels of hsa-mir-135a in the eutopic endometrium of endometriosis patients were detected, compared to controls [ 6 ]. This was confirmed by a subsequent study, which also found that hsa-mir-135a was upregulated in eutopic endometrium [ 46 ]. While in the first study, the hsa-mir-135a expression was reported to be increased in the proliferative phase [ 6 ], in the second study, expression was upregulated in the secretory phase, although the proliferative phase showed a similar trend [ 46 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In the biggest study, which included 50 controls and 32 eutopic samples, elevated levels of hsa-mir-135a in the eutopic endometrium of endometriosis patients were detected, compared to controls [ 6 ]. This was confirmed by a subsequent study, which also found that hsa-mir-135a was upregulated in eutopic endometrium [ 46 ]. While in the first study, the hsa-mir-135a expression was reported to be increased in the proliferative phase [ 6 ], in the second study, expression was upregulated in the secretory phase, although the proliferative phase showed a similar trend [ 46 ].…”
Section: Discussionsupporting
confidence: 63%
“…This was confirmed by a subsequent study, which also found that hsa-mir-135a was upregulated in eutopic endometrium [ 46 ]. While in the first study, the hsa-mir-135a expression was reported to be increased in the proliferative phase [ 6 ], in the second study, expression was upregulated in the secretory phase, although the proliferative phase showed a similar trend [ 46 ]. An independent study focusing solely on endometriosis patients found that hsa-mir-135a expression was significantly reduced in ectopic compared to eutopic endometrium [ 47 ].…”
Section: Discussionsupporting
confidence: 63%
“…The impact of miR-135 on endometrial cancer was contradictory in the literature. Wang J. et al (2020) revealed that miR-135a promoted proliferation, migration, and invasion and induced chemoresistance of endometrial cancer cells, but ( Mirabutalebi et al, 2018 ) found miR-135a acted as a tumor suppressor by targeting ASPH in endometrial cancer ( Chen et al, 2019 ; Wang J. et al, 2020 ). A positive correlation was also observed between the expression of miR-135a and endometriosis lesions, which is a disease also referring migration of the endometrium ( Mirabutalebi et al, 2018 ; Petracco et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“… Wang J. et al (2020) revealed that miR-135a promoted proliferation, migration, and invasion and induced chemoresistance of endometrial cancer cells, but ( Mirabutalebi et al, 2018 ) found miR-135a acted as a tumor suppressor by targeting ASPH in endometrial cancer ( Chen et al, 2019 ; Wang J. et al, 2020 ). A positive correlation was also observed between the expression of miR-135a and endometriosis lesions, which is a disease also referring migration of the endometrium ( Mirabutalebi et al, 2018 ; Petracco et al, 2019 ). The expression of miR-449b was markedly reduced in type II endometrial cancer tissues, and its reduction was associated with endometriosis lesions via endometrial stromal cell proliferation and angiogenesis ( Braza-Boils et al, 2014 ; Ye et al, 2014 ; Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TP53 has been validated as a miR-125b target in several investigations by different methods, including reporter assay, western blot, and qPCR (23). However, the dysregulation of miR-125b and TP53 between ectopic and eutopic endometrial samples has rarely been investigated (28).…”
Section: Introductionmentioning
confidence: 99%